DEFINING THE IDEAL COMPETENCY MODEL FOR THE UNITED NATIONS MILITARY OBSERVERS (STUDY ON THE INDONESIAN MILITARY OBSERVERS) - Syaiful Anwar (The Republic of Indonesia Defense University, 2019)
A military observer is a military officer from a certain country who is deployed as part of a United Nations Peacekeeping Mission. The purpose of this study is to define an ideal competency model for the UN military observers of the Indonesian military by considering certain characteristics embedded in superior military observers that distinguish them from the non-superior ones. This study applied several data collecting techniques such as behavioral event interviews, observation, and library study. Two types of analysis, namely: content analysis and discriminant analysis are utilized to create data weighting and to discover the differentiating characteristics. From this study, it can be concluded that there is a very close and significant relationship between the competency and performance of the UN military observers from Indonesia. Those in the superior category do have three strong differentiating competencies, namely: initiative, relationship building, and impacts and influence production. And then this study also found an ideal competency model for a UN military observer, where the model consists of the three competencies plus eight other competencies, namely: team working, self-controlling, local language skill, local culture knowledge, vehicle driving skill, military knowledge and skills, diplomacy and negotiation skills, and administrative skills.Keywords: Competency, Competency model, Military observer, Recruitment, UN Peacekeeping